Gulliver and the Gentle Reader - Claude RAWSON (E-REA)
The satire in Swift’s anatomy of the human animal in Gulliver’s Travels is unusually radical, comprehensive and aggressive. In the first three books it conventionally attacks humans for what they do, but at the end of book III and throughout book IV humans are attacked for what they are. From the beginning, the reader is wrongfooted by an unusually quarrelsome intimacy on the part of the narrative, and a constantly shifting instability in the register of the irony. The naïve Gulliver’s praise of humanity, as well as his deranged condemnation of it in the final book, are both separate from the implied voice of the satirist, which always makes itself felt. But the reader is left uncertain as to the exact degree and tone of this separation. While knowing that the details of Gulliver’s enraged diatribes are substantiated by the facts of the narrative, the unhinged nature of the speaker’s voice must be discounted as being in Timon’s manner which Swift explicitly disavowed in a famous letter to his friend Pope. The reader is thus left without the comfort and foothold of an extreme denunciation which could be dismissed as self-disarming precisely because the implied satirist’s voice is disengaged from the character. This is part of what Swift meant when he told Pope that the story was designed to vex the world rather than divert it.